The Calvin and Hobbes tenth anniversary book - Watterson, Bill. (New York : Scholastic, Inc., 1995)
A collection of cartoons from the comic strip "Calvin and Hobbes," celebrating the tenth anniversary of the strip's publication.
Keywords: Comic books, strips, etc. -- United States; Calvin and Hobbes (Fictitious characters)